2005
DOI: 10.1242/jcs.02612
|View full text |Cite
|
Sign up to set email alerts
|

Set1- and Clb5-deficiencies disclose the differential regulation of centromere and telomere dynamics inSaccharomyces cerevisiaemeiosis

Abstract: The entry into meiosis is characterized by a lengthy premeiotic S phase and a reorganization of the nuclear architecture. Analysis of centromere and telomere dynamics in wild-type Saccharomyces cerevisiae meiosis suggests that resolution of vegetative centromere and telomere clusters are independent events differently connected to premeiotic S phase. Absence of the B-type cyclin Clb5 or the Set1 histone methyltransferase leads to a delay of premeiotic S phase by separate mechanisms. In clb5Δ cells, centromere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…For instance, it has been shown that replication at centromeric regions causes disassembly of kinetochores and detachment of centromeres from the spindle pole prior to recapture by microtubules (Kitamura et al 2007). In addition, telomere repositioning and bouquet formation during the transition to a meiotic cell cycle is conserved among eukaryotes, and in yeast is shown to be caused by a DNA replicationcoupled event (Trelles-Sticken et al 2005). Emerging data suggest that mechanisms involved in positioning of telomeres may be conserved from yeast to vertebrates, at least to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that replication at centromeric regions causes disassembly of kinetochores and detachment of centromeres from the spindle pole prior to recapture by microtubules (Kitamura et al 2007). In addition, telomere repositioning and bouquet formation during the transition to a meiotic cell cycle is conserved among eukaryotes, and in yeast is shown to be caused by a DNA replicationcoupled event (Trelles-Sticken et al 2005). Emerging data suggest that mechanisms involved in positioning of telomeres may be conserved from yeast to vertebrates, at least to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle mechanism that alters telomere localization in late interphase has not previously been characterized. Interestingly, however, it has been suggested that reorganization of telomeres following premeiotic S phase may be linked to DNA replication (Trelles-Sticken et al 2005).…”
mentioning
confidence: 99%
“…Conversely, lysine demethylases have been identified for H3 Lys4 and H3 Lys36; Jhd2p demethylates H3 Lys4 (Liang et al 2007;Seward et al 2007), while Jhd1p, and the paralogs Rph1p and Gis1p target H3 Lys36 for demethylation (Tu et al 2007). Yeast harboring deletions of these enzymatic regulators of methylation have a myriad of phenotypes including loss of telomeric silencing and ribosomal DNA (rDNA), sensitivity to cellular stressors, and misregulation of apoptosis and meiosis (Singer et al 1998;San-Segundo and Roeder 2000;Deutschbauer et al 2002;Krogan et al 2002;Santos-Rosa et al 2002;Boa et al 2003;Schaft et al 2003;Sollier et al 2004;Carrozza et al 2005;Fingerman et al 2005;Morohashi et al 2005;Trelles-Sticken et al 2005;Merker et al 2008;Walter et al 2014).…”
mentioning
confidence: 99%
“…Very little is known about how changes in chromatin structure affect meiosis or how these changes are controlled in any organism. Studies in budding yeast have shown that mutations in Set1, which is responsible for methylation of H3 lysine 4, block bouquet formation (Trelles-Sticken et al, 2005b). Likewise, telomere clustering at the spindle pole body during meiosis requires the methylation of H3 on lysine 9 in S. pombe (Tuzon et al, 2004).…”
Section: What Is the Role Of Ask1 In Meiosis?mentioning
confidence: 99%
“…For example, the absence of the B-type cyclins Clb5 and Clb6, which are required for premeiotic S phase in budding yeast, leads to defects in double-strand break (DSB) induction, recombination and synaptonemal complex (SC) formation (Smith et al, 2001;Stuart and Wittenberg, 1998). Deletion of the histone methyltransferase Set1 leads to a delay in premeiotic S-phase and subsequent alterations in centromere and telomere distribution (Trelles-Sticken et al, 2005b). Likewise, defects in During early stages of meiotic prophase I the nucleus undergoes considerable reorganization, including the clustering of telomeres, the release of contacts between chromosomes and the nuclear membrane, the reorganization of the nucleolus, and chromatin remodeling.…”
Section: Introductionmentioning
confidence: 99%